Is State Feminism the Key to Gender Equality? - Kamaly, Nadine Mohamed (AUC Knowledge Fountain, 2023)
“The male point of view forces itself upon the world as a way of apprehending it. Perspectives from the male standpoint enforces a woman's definition, encircles her body, circumlocutes her speech, and describes her life” (Mackinnon, 1983, 636). How the world views women is sometimes out of their hands. Ogasawara (1999) explains that “there is a multiplicity of socially acceptable images of Japanese women today” (pg.87). Throughout this thesis, I will explore the several, but limited, images that Japanese society has rendered acceptable for women. I will also examine how Japanese State Feminism aims to give women the opportunity to have agency to change those images. In this thesis, I use the term State Feminism to refer to ‘Femocrats’, i.e. feminists who are policymakers and thus come to play a role in presenting women’s issues and demands within the policymaking sector in the state in order to help better represent women’s demands and close the gender gap between both sexes. In this thesis, I hypothesize that based on the fact that Japan is a strongly conservative society that encompasses a good number of conservative elites and policymakers, the creation of national bureaus and unions, supported by either specific movements or in a specific context (such as international pressure, economic concerns), has put Japanese feminism in a position in which said organs function according to the context they are in. Thus, this leads us to question whether State Feminism can solely help feminists achieve gender equality. Throughout this thesis, I deduce that State Feminism on its own has not been enough to achieve gender equality. It was rather certain conditions that have led even conservative, patriarchal policymakers to add women-friendly policies, paving the way for State Feminism to take root, even if it did not fully developed.